2019
DOI: 10.1186/s12885-019-6168-1
|View full text |Cite
|
Sign up to set email alerts
|

Female sex is associated with a lower risk of bone metastases and favourable prognosis in non-sex-specific cancers

Abstract: BackgroundThe objectives were to investigate the disparity in the prevalence of bone metastases (BM) between the sexes and to assess the effect of female sex on the development and prognosis of BM.MethodsCases of invasive non-sex-specific cancers diagnosed between 2010 and 2015 in the Surveillance, Epidemiology, and End Results (SEER) program were used. The prevalence of BM was calculated by combining the prevalence of BM among different cancers. Multivariable logistic regression and proportion hazard regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Under these hypoxic conditions, tumor cells can switch to collecting unsaturated fatty acids from the microenvironment ( 9 ), and it could be proposed that, although highly speculative, the increased unsaturated fatty acids we show within the spine and pelvis compared to the femora and tibia might be a part of the explanation why skeletal metastases are preferentially located within the axial skeleton ( 55 ). Furthermore, it could be postulated, again highly speculatively, that the gender-associated differences in BMAT within the spine, pelvis, and proximal femur, i.e., areas containing red bone marrow, could be part of the explanation for the observation that female patients are less likely to have skeletal metastasis ( 56 ) and more likely to develop osteoporosis. Future research on the interaction between BMAT and bone metabolism or skeletal metastasis should take these differences between the axial and appendicular skeleton into consideration, as results on BMAT acquired from the iliac crest might provide different results compared to BMAT acquired from the proximal femur.…”
Section: Discussionmentioning
confidence: 99%
“…Under these hypoxic conditions, tumor cells can switch to collecting unsaturated fatty acids from the microenvironment ( 9 ), and it could be proposed that, although highly speculative, the increased unsaturated fatty acids we show within the spine and pelvis compared to the femora and tibia might be a part of the explanation why skeletal metastases are preferentially located within the axial skeleton ( 55 ). Furthermore, it could be postulated, again highly speculatively, that the gender-associated differences in BMAT within the spine, pelvis, and proximal femur, i.e., areas containing red bone marrow, could be part of the explanation for the observation that female patients are less likely to have skeletal metastasis ( 56 ) and more likely to develop osteoporosis. Future research on the interaction between BMAT and bone metabolism or skeletal metastasis should take these differences between the axial and appendicular skeleton into consideration, as results on BMAT acquired from the iliac crest might provide different results compared to BMAT acquired from the proximal femur.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Ma et al reported that female sex was associated with a lower risk of bone metastasis in digestive system cancers. [ 21 ] Sex hormone levels differ between men and women, and musculoskeletal health may be the primary cause of these differences. [ 22 ] Differences in lifestyle factors may also account for these outcomes; for example, men are 1.5-times more likely than women to smoke.…”
Section: Discussionmentioning
confidence: 99%
“…The dots represent outliers with poorer MFS in our study cohort. In a recent study, female sex was proposed to be associated with a lower risk of BM [41]. This prognostic factor was also found to be relevant by Zhang et al, who included these factors in a predictive scoring system [42].…”
Section: Bone Metastasis-free Survivalmentioning
confidence: 81%